Ancoramento de complexos metálicos em matriz de sílica para estudo na eficiência de geração de oxigênio singleto - Oliveira, Andrelane Ribeiro (2023)
Silica matrices possess interesting properties that render them excellent supports for other molecules. The literature reports the immobilization of complex ruthenium ions to synthesize various materials and applications. Immobilizing photosensitizers onto specific solid carriers, used for catalytic generation of reactive oxygen species, facilitates the degradation of organic compounds in water treatment. This approach enables heterogeneous reactions and allows for the recyclability of the catalytic system. Consequently, the aim of this study was to synthesize silica spheres modified with the complex ruthenium ions Ru(bpy)2(mbpy-ant)2 and [Ru(bpy)(mbpy-ant)Cl2], where bpy stands for 2,2'-bipyridine, and mbpy-ant stands for 4'-methyl-N-(anthracen-2-yl)-[2,2'-bipyridine]-4-carboxamide. These modifications aimed to enhance singlet oxygen production for remediating water residues from dye degradation. The silica materials were characterized through vibrational spectroscopy in the infrared region, diffuse reflectance spectroscopy in the UV-Vis region, and Zeta potential measurements. The complexes' characterization included electronic spectroscopy in the ultraviolet and visible regions, revealing MLCT bands at 458 nm for Ru(bpy)2(mbpy-ant)2 and 581 nm for [Ru(bpy)(mbpy-ant)Cl2]. Additional characterizations involved vibrational spectroscopy in the infrared region, cyclic voltammetry, and 1H NMR, establishing redox potentials of RuIII/II as E1/2 = +1.34 V and E1/2 = +0.455 V vs Ag/AgCl. The singlet oxygen detection assay, using DPBF, exhibited an outstanding quantum yield of 0.99 for the complex Ru(bpy)2(mbpy-ant)2. Furthermore, qualitative evidence indicated that the anchored complexes on the silica matrices generated singlet oxygen. The utilization of these photosensitizing systems for organic pollutant degradation through singlet oxygen attack mechanisms will be explored in future studies.